2015
DOI: 10.1080/01932691.2015.1048460
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Investigation of the Micellar Behavior of a Diblock (PEO)62-b-(PBO)33Copolymer in Water and its Interaction with Ionic Surfactants

Abstract: The physicochemical investigations on the associative, micellar and thermodynamic properties of a diblock (PEO) 62 -b-(PBO) 33 copolymer in aqueous medium and its interaction with ionic surfactants were carried out by using surface tensiometry, laser light scattering and steady-state fluorescence spectroscopy. Surface tension and fluorescence measurements were used to find out the critical micelle concentration (CMC) and related thermodynamic parameters of micellization copolymer at various temperatures. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…A large number of these applications are concerned with the formation of micelles and hence, micellization of block copolymer has generated substantial interest in the literature [ 7 ]. The interaction along with the aggregation behavior of mixed surfactants in solution and at interfaces has been rigorously investigated using various techniques such as small angle neutron scattering (SANS), dynamic light scattering (DLS), fluorescence, surface tension, viscosity, conductivity, and cyclic voltammeter [ 8 , 9 , 10 , 11 , 12 ]. As Pluronics ® are often employed in complex environments, for instance, in presence of other additives or amphiphile, studies on their effect on solution behavior of copolymers can help to optimize properties based on performance for various applications.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of these applications are concerned with the formation of micelles and hence, micellization of block copolymer has generated substantial interest in the literature [ 7 ]. The interaction along with the aggregation behavior of mixed surfactants in solution and at interfaces has been rigorously investigated using various techniques such as small angle neutron scattering (SANS), dynamic light scattering (DLS), fluorescence, surface tension, viscosity, conductivity, and cyclic voltammeter [ 8 , 9 , 10 , 11 , 12 ]. As Pluronics ® are often employed in complex environments, for instance, in presence of other additives or amphiphile, studies on their effect on solution behavior of copolymers can help to optimize properties based on performance for various applications.…”
Section: Introductionmentioning
confidence: 99%
“…The observed positive Δ S 0 m values for TTAB + CMT accumulation may be explained by two issues. The first one involves the demolishing of iceberg configurations by moving the hydrated hydrophobic portion into the micellar core 37 of a TTAB + CMT combination. Another factor is that, in contrast to the aqueous surroundings, the degree of rotational flexibility of hydrophobic parts rises in the micellar interior.…”
Section: Resultsmentioning
confidence: 99%
“…and surfactants occurred which signicantly modied the aggregation character of the surfactants. [34][35][36][37][38][39] Measurement of conductivity, [34][35][36] surface tension, [36][37][38] light scattering techniques, 35,37,38 steady-state uorescence spectroscopy, 36,37 simple and differential UV/visible spectroscopic studies, 39 and small-angle neutron scattering (SANS) 40 methods were used to evaluate the physicochemical features of the aggregation process of the solutes-surfactant system. In the literature, several studies have revealed the mode of interaction of surfactants and HTs, emphasizing the widespread applications in antibacterial medicines.…”
Section: Introductionmentioning
confidence: 99%